Analisis Pengaruh Infrastruktur Listrik, Jalan Dan Kesehatan Terhadap Produk Domestik Regional Bruto Di Kabupaten Sidoarjo - Yurike Aldona; Wiwin Priana Primandhana; Muhammad Wahed (Universitas Batanghari Jambi, 2021)
Gross Regional Domestic Product (GDP) is one of the economic indicators according to various economic instruments in which clearly visible macro-economic conditions of a region. Infrastructure is the most primary public infrastructure in supporting a country's economic activities, and the availability of infrastructure greatly determines the level of efficiency and effectiveness of economic activities. This study aims to analyze how much electricity, road, and health infrastructure affects gross regional domestic product in Sidoarjo Regency. This research covers the area of Sidoarjo Regency. This study uses secondary data obtained from the Central Statistics Agency with a period of 15 years from 2005-2019. The analysis technique used is Multiple Linear Regression Analysis with Ordinary Least Square (OLS) model using computer tools SPSS program (Statistic Program For Social Science) Version 13.0 that shows the influence between free variables and bound variables. The end result is that electricity infrastructure variables have a positive and significant influence on gross regional domestic product in Sidoarjo Regency. Variable road infrastructure and health infrastructure have a positive but insignificant influence on gross regional domestic product in Sidoarjo Regency.